2015
DOI: 10.1007/s11999-015-4385-8
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived Mesenchymal Stem Cells Are Phenotypically Superior for Regeneration in the Setting of Osteonecrosis of the Femoral Head

Abstract: Background Bone marrow-derived mesenchymal stem cells (bmMSCs) have been used as a cellular therapeutic option for treatment of osteonecrosis of the femoral head. However, use of bmMSCs as a treatment adjuvant for orthopaedic disorders in general has achieved limited success. Adipose-derived MSCs (aMSCs) may be a moreefficient regenerative cell source given their greater quantity and protection from physiologic stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…Adipose-derived mesenchymal stem cells (ADSCs) have been suggested to be superior to BMSCs in some orthopedic applications (Wyles and others 2015). However, most studies of this type have been conducted in subjects less than 60 years of age.…”
Section: Treating Age-related Adipose Tissue Dysfunctionmentioning
confidence: 99%
“…Adipose-derived mesenchymal stem cells (ADSCs) have been suggested to be superior to BMSCs in some orthopedic applications (Wyles and others 2015). However, most studies of this type have been conducted in subjects less than 60 years of age.…”
Section: Treating Age-related Adipose Tissue Dysfunctionmentioning
confidence: 99%
“…Studies from OA and osteonecrosis patients have shown the most prominent impact on bone marrow-derived MSCs, with adipose-derived MSCs maintaining a greater level of functionality. 47 This observation may be secondary to the intense physiologic stress of the bone marrow microenvironment relative to comparatively quiescent adipose tissue. Differential dysfunction of MSCs by disease and tissue source has important implications for therapeutic implementation of cell transplantation therapies.…”
Section: Msc Derangements In Oa and Related Conditionsmentioning
confidence: 99%
“…Although MSCs from different tissue sources have been shown to be similar in morphology and function, subtle differences may exist in their immunomodulatory profile which may be attributable to microenvironmental niche, method of harvest, or ontogenic age [2426]. These differences may play a role in MSC reparative properties, and conflicting studies exist [2729]. We therefore hypothesized that: (1) MSCs would increase survival and mesenteric perfusion, preserve intestinal histological architecture, and limit intestinal inflammation following intestinal ischemia and reperfusion injury (I/R), and 2) MSCs harvested from different source tissues would have equivalent protective properties to the intestine following I/R.…”
Section: Introductionmentioning
confidence: 99%